2023
DOI: 10.1002/aenm.202300172
|View full text |Cite
|
Sign up to set email alerts
|

Dry Pre‐Lithiation for Graphite‐Silicon Diffusion‐Dependent Electrode for All‐Solid‐State Battery

Abstract: The graphite/silicon-based diffusion-dependent electrodes (DDEs) are one of the promising electrode designs to realize high energy density for all-solid-state batteries (ASSBs) beyond conventional composite electrode design. However, the graphite/silicon-based electrode also suffers from large initial irreversible capacity loss and capacity fade caused by significant volume change during cycling, which offsets the advantages of the DDEs in ful-cell configuration. Herein, a new concept is presented for DDEs, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…6e compares the performance of this work with the published literature on Si-ASSBs in terms of areal capacity and ICE (Table S1, ESI†). 13–15,23–29 It is found that the performances of the Si-ASSBs depend on not only the modification of the Si anode, but also the stability of the SE and cathode. For ICE, the LCO and coated NCM were largely comparable and both superior to that of LFP and normal NCM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6e compares the performance of this work with the published literature on Si-ASSBs in terms of areal capacity and ICE (Table S1, ESI†). 13–15,23–29 It is found that the performances of the Si-ASSBs depend on not only the modification of the Si anode, but also the stability of the SE and cathode. For ICE, the LCO and coated NCM were largely comparable and both superior to that of LFP and normal NCM.…”
Section: Resultsmentioning
confidence: 99%
“…Although the growth of lithium dendrites can be further inhibited by the addition of highly conductive materials, such as hard carbon and graphite, the ICEs of Si-ASSBs in these reported works are still below 90% due to side reactions, and the insufficient effective capacity is much lower than that of liquid lithium-ion batteries. 14,15,23–29…”
Section: Introductionmentioning
confidence: 99%
“…Typically speaking, complete prelithiation of Si/C anodes possesses several advantages. Besides compensating for the massive Li + loss for SEI formation, the volume expansion of Si can occur sufficiently before battery operation, avoiding the undesirable structure collapse of the anode during cycling. As a result, the Coulombic efficiency and cycle life of the battery are supposed to be promoted either. Figure a,b shows the results of the EIS plots of half-cells equipped with pristine and lithiated Si/C electrodes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Metal oxides possess the properties of a semiconductor with a particular band gap and high crystallinity, and are potentially applied in photocatalysis, gas sensing, photothermal therapy, and catalyst carriers. Mesoporous metal oxides with high porosity and large exposure of surface unsaturated metal atoms can definitely enhance their properties and thus improve their performance. However, the design synthesis of mesoporous metal oxides with high crystallization is a great challenge because the high-temperature crystallization usually inevitably induces mesostructure collapse.…”
Section: Introductionmentioning
confidence: 99%